THE BARGAINING POLITICS: DETERMINING REGIONAL PUBLIC POLICY IN FORMULATING THE SAMISAKE REVOLVING FUND PROGRAM IN BENGKULU CITY, INDONESIA; DERYBŲ POLITIKA: REGIONINĖS VIEŠOSIOS POLITIKOS NUSTATYMAS FORMUOJANT SAMISAKE APYVARTINIO FONDO PROGRAMĄ BENGKULU MIESTE, INDONEZIJOJE - Aminudin, Achmad; Darmi, Titi; Pramusinto, Agus; Mujtahid, Iqbal Miftakhul (2023)
The political arena influences the selection of an alternative policy for Samisake Revolving Fund program. In this phase, various interests affect the policy outcome, including conflict and bargaining positions among policymakers. Therefore, this study aimed to examine public participation in policy formulation for the Samisake Revolving Fund program in Bengkulu City, Indonesia. A qualitative method was used with a case study approach to the policy design, as well as typical conditions and variables. Data were collected by interviewing seven informants of five stakeholder elements and analyzed using flowing analysis. The results indicated high community involvement in the public policy formulation process that entails pushing issues into the policy agenda. The best policy alternative should satisfy all interested parties. Additionally, the policy was established by issuing the Regional Regulation draft on allocating the funding. This Regional Regulation should be accepted and implemented by all parties transparently with accountability to increase community participation and empowerment. The policy process displays a complex interaction among the policymakers. These policymakers include the executives of the Bengkulu City government from the Regional Technical Unit, community leaders and organizations, NGOs, and university academics. The interaction influences choices and policy decisions by creating conflict and tension in discussing the draft of Samisake Fund Regional Regulation. Therefore, future studies could examine stakeholder network participation in policy formulation and strengthening inter-institutional capacity to avoid conflict. © 2023 Mykolas Riomeris University. All rights reserved.